Barriers to midwives and nurses addressing mental health issues with women during the perinatal period: The Mind Mothers study. Issue 9 (13th March 2018) - Higgins, Agnes; Downes, Carmel; Monahan, Mark; Gill, Ailish; Lamb, Stephen A; Carroll, Margaret
Abstract : Aims and objectives: To explore barriers to midwives and nurses addressing mental health issues with women during the perinatal period. Background: Perinatal mental health is considered an important public health issue with health policy internationally identifying the importance of psychological support for women in the perinatal period. Midwives and primary care nurses are ideally positioned to detect mental distress early, but evidence suggests that they are reluctant to discuss mental health issues with women during pregnancy or in the postnatal period. Design: The research used a descriptive design. Methods: A total of 809 midwives and nurses completed an anonymous, online or hard copy survey. Designed by the research team, the survey listed 26 potential barriers to the provision of perinatal mental health care. Results: Participants identified organisational factors as presenting the greatest barriers. Organisational barriers included lack of perinatal mental health services, absence of care pathways, heavy workload, lack of time, lack of privacy and not seeing women regularly enough to build a relationship. Over 50% of participants identified practitioner‐related barriers, such as lack of knowledge on perinatal mental health and cultural issues; lack of skill, in particular, skills to respond to a disclosure of a mental health issue; and fears of causing women offence and distress. Findings also indicated that the context of care and education influenced the degree to which participants perceived certain items as barriers. Conclusions: Midwives and primary care nurses encounter many organisational‐ and practitioner‐related barriers that negatively impact on their ability to incorporate mental health care into their practice. Relevance to clinical practice: Midwifery and nursing services need to develop strategies to address system‐ and practitioner‐related barriers, including the development of services and care pathways, and the provision of culturally sensitive education on perinatal mental health in order to support practitioners to address issues with confidence and competence.